2017
DOI: 10.1039/c7ra04742h
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of high degree crystallinity zeolite Y with micro–meso–macroporous structure

Abstract: Template-free synthesis of zeolite Y with hierarchical porous structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The material revealed high activity in the multicomponent reaction of propanol with formaldehyde and ammonia toward 3,5-dimethylpyridine with a selectivity of 95%. [311] Nanozeolites and Their Assembly: Regarding zeolite Y nanoassemblies, two noteworthy works have been published that both use a template-free strategy and thus focus on kinetic regulation of the crystallization process. The first work by Ferdov synthesized zeolite Y nanosheet assemblies by repetitive branching of hierarchically arranged FAU nanolayers.…”
Section: Zeolite Ymentioning
confidence: 99%
“…The material revealed high activity in the multicomponent reaction of propanol with formaldehyde and ammonia toward 3,5-dimethylpyridine with a selectivity of 95%. [311] Nanozeolites and Their Assembly: Regarding zeolite Y nanoassemblies, two noteworthy works have been published that both use a template-free strategy and thus focus on kinetic regulation of the crystallization process. The first work by Ferdov synthesized zeolite Y nanosheet assemblies by repetitive branching of hierarchically arranged FAU nanolayers.…”
Section: Zeolite Ymentioning
confidence: 99%
“…Travkina et al [10] proposed to generate macro-and mesoporous zeolite Y by modification of granules that contain a mixture of microporous zeolite with kaolin. After calcination, the granules were crystallized in sodium silicate solution, ion-exchanged for NH 4 + , dried, and calcined in dry air.…”
Section: Hierarchical Zeolites Y Obtained By Assembly Of Zeolitic Grainsmentioning
confidence: 99%
“…One of them was the synthesis of extra-large pore zeolites [5,6]. Another one was the preparation of zeolite nanoparticles [7][8][9] or assembly of zeolitic micrograins producing micro-meso-macroporous structures [10,11]. A very effective way was the synthesis of hierarchical zeolites containing more than one level of pores.…”
Section: Introductionmentioning
confidence: 99%
“…The zeolite Beta obtained by using the seed assisted approach has been widely used for different applications such as; gas adsorption [26a] and catalysis. [26b] In addition to Beta zeolite, the other zeolite frameworks such as; ZSM-5, [27] SSZ-13, [28] CHA, [29] NaY, [30] SUZ-4, [31] LEV, [32] and MTW [33] zeolite have also been prepared using the seed-assisted strategy (Table 1, entries [16][17][18][19][20][21][22]. These zeolite frameworks have been explored for different organic transformations and gas separation.…”
Section: Seed-assisted Synthesismentioning
confidence: 99%
“…These zeolite frameworks have been explored for different organic transformations and gas separation. [27][28][29][30][31][32][33] The seed assisted method has also been reported for the synthesis of selective zeolite framework by using the seed of other zeolite frameworks. Xiao et al have reported the selective synthesis of ZSM-34 using a small proportion of zeolite L in the synthesis composition of ZSM-34 (( Table 1, entry 23).…”
Section: Seed-assisted Synthesismentioning
confidence: 99%